Aquaculture role in global food security with nutritional value: a review - Pradeepkiran, Jangampalli Adi (Transl Anim Sci, 2019)
Food security is the main path to develop the socioeconomic status in any country in the world to defeat malnutrition. The present scenario in an under developed countries are still facing this problem. Hence the human nutrition deficiencies focus on the importance of animal protein in their regular diet. To overcome this problem, fisheries contribute a significant amount of animal protein to the diets of people worldwide. The aquatic animals are the highly nutritious and cheapest protein sources, which serves as a valuable supplement in diets by providing essential vitamins, proteins, micronutrients, and minerals, for the poor people. Aquaculture is playing a vital role in the developing countries in national economic development, and global food supply. Food and agricultural organization (FAO) declared that this aquaculture has the continuous potentiality to create a developmental goals for the country economy and better human welfare.